Efeito residual de fontes de fósforo nos atributos químicos do solo, nutrição e produtividade de biomassa da cana-de-açúcar - Caione, Gustavo [UNESP]; Fernandes, Francisco M. [UNESP]; Lange, Anderson (Revista Brasileira de Ciencias Agrarias, 2013)
In tropical regions, the residual effect of phosphate fertilizer source is of crucial importance. This study aimed to evaluate the effects of application of P sources in chemical properties of soil, nutrition and productivity of sugarcane plant and during the first and second ratoon. The sources of P applied in furrows at planting were, triple superphosphate, Arad phosphate, bone meal (100 kg ha-1 P2O5 total) and a control without P, the varieties of sugarcane studied were IAC86-2480 and SP79-1011. A randomized block design in a 4 × 2 factorial was used, with four replications. The study was conducted in the municipality of Alta Floresta-MT, Brazil, in Typic Hapludox. After each cutting, in soil P content, pH and Ca were evaluated. In the plant, the production of green and dry matter of shoots, the concentration of P in the biomass harvested, the export of P and agronomic efficiency of the sources of P were determined. The bone meal had a higher agronomic efficiency resulted in greater accumulation and export of P by crop, higher content of available Ca and P and increase soil pH. The Arad reactive phosphate increased its agronomic efficiency between crop cycles.
Residual effect of phosphorus sources in soil chemical properties, nutrition and biomass productivity of sugarcane
Keywords: Agronomic efficiency; Bone meal; Phosphorus fertilization; Saccharum spp